A Comparative Study of the Availability of Electric Buses in the Public Transport System - Andrzej Niewczas; Łukasz Mórawski; Ewa Dębicka; Joanna Rymarz; Dariusz Kasperek; Piotr Hołyszko (Applied Sciences)
This study deals with the assessment of the progress of the electromobility programme with regard to the technical availability of public transport buses. The aim of this study was to conduct a comparative assessment of the availability of electric buses in relation to diesel buses (of analogous capacity). The study was carried out in real operating conditions using the example of Lublin city. Over a period of 33 months, the availability of electric buses and diesel buses was tested in a sample of 18 vehicles for each type of bus. Availability indices were compared using the method of variance analysis. It was found that electric buses had a higher level of availability and no trend during the study period. The applied research method can be used in operational practice to monitor the risks associated with vehicle failure rates and the continuity of fleet operations.